A Review on Multicommodity Urban Evacuation Problem - Acharya, Gopal Prasad; Khadka, Shree Ram (Journal of Institute of Science and Technology, 2016)
Urban evacuation regards as a critical course of action that helps to re-locate the maximum number of people and property from the disaster zone of the urban area to the safe zone within the shortest possible time. Multi-commodity urban evacuation problem (MCUEP) explores and identifies the re-construction of the traffic routes to be followed in evacuation with the mobility of two or more types of the vehicles allowing two way streets. The idea of the paper is to introduce a multi-commodity urban evacuation traffic routing modeling with the bus commodity and the vehicle commodity in the street segment and intersection segment where the crossing and merging cannot be prohibited. The evacuation is made effective by sending and re-sending the buses (if necessary) and using the personal vehicles for once. The paper will give a review of MCUEP as the state of the art basically designed as a mixed integer model functioning as the remedy of the shortcomings of one-way evacuation model and put forwards a brief discussion of the solution approaches. Journal of Institute of Science and Technology Volume 21, Issue 1, August 2016, page: 19-27